2022
DOI: 10.3390/antiox11040637
|View full text |Cite
|
Sign up to set email alerts
|

Ripening-Induced Changes in the Nutraceutical Compounds of Differently Coloured Pepper (Capsicum annuum L.) Breeding Lines

Abstract: To date, several research studies addressed the topic of phytochemical analysis of the different coloured pepper berries during ripening, but none discussed it in the case of purple peppers. In this study we examine whether the anthocyanin accumulation of the berries in the early stages of ripening could result in a higher antioxidant capacity due to the elevated amount of polyphenolic compounds. Therefore, enzymatic and non-enzymatic antioxidant capacity was measured in four distinct phenophases of fruit matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…However, in the later stage, the content of metabolites, such as capsaicinoids (capsaicin and dihydrocapsaicin), amino acids (leucine, isoleucine, proline, and phenylalanine), and kaempferol glycosides, increased significantly. In contrast to the above findings reporting higher antioxidant activity in matured stages, some studies reported higher antioxidant activity in fully developed green stage (Dobón‐Suárez et al., 2021; Kappel et al., 2008; Kovacs et al., 2022; Oney‐Montalvo et al., 2020; Thuphairo et al., 2019), which reflects dynamic changes in antioxidant capacity during pepper fruit development. Thus, these studies indicate the importance of considering the maturity stage of pepper at the time of harvesting for maximum nutritional and functional benefits of pepper, which also ultimately affects consumer preferences.…”
Section: Factors Influencing Antioxidant Activity Of Peppermentioning
confidence: 83%
See 3 more Smart Citations
“…However, in the later stage, the content of metabolites, such as capsaicinoids (capsaicin and dihydrocapsaicin), amino acids (leucine, isoleucine, proline, and phenylalanine), and kaempferol glycosides, increased significantly. In contrast to the above findings reporting higher antioxidant activity in matured stages, some studies reported higher antioxidant activity in fully developed green stage (Dobón‐Suárez et al., 2021; Kappel et al., 2008; Kovacs et al., 2022; Oney‐Montalvo et al., 2020; Thuphairo et al., 2019), which reflects dynamic changes in antioxidant capacity during pepper fruit development. Thus, these studies indicate the importance of considering the maturity stage of pepper at the time of harvesting for maximum nutritional and functional benefits of pepper, which also ultimately affects consumer preferences.…”
Section: Factors Influencing Antioxidant Activity Of Peppermentioning
confidence: 83%
“…For example, pepper fruits show the development of distinct colors during different stages of development, such as green, yellow, red, orange, brown, and violet, and green peppers contained high levels of chlorophyll a, free all‐ trans ‐lutein, and carotenoids along with higher levels of polyphenols, proanthocyanins, and total flavonoids; color breaker stage had a higher content of dehydroascorbic acid; matured red stage had a high content of carotenoids (capsanthin, capsorubin, and capsanthin 5,6‐epoxide carotenoids), oligomeric anthocyanins, vitamin C and provitamin A; yellow and orange peppers contained high levels of flavonoids and oligomeric anthocyanins, zeaxanthin, β‐cryptoxanthin, lutein, and α‐ and β‐carotene, whereas purple or violet peppers had high polyphenolic and flavonoid contents along with the main anthocyanin, delphinidin‐3‐ trans coumaroylrutinoside‐ 5‐glucoside (Cervantes‐Paz et al., 2012; Howard, 2001; Jimenez et al., 2003; Kovacs et al., 2022; Marin et al., 2004; Martinez et al., 2005; Sadilova et al., 2006; Shukla et al., 2016; Sun et al., 2007; Thuphairo et al., 2019). Further, most of the studies assessing the antioxidant activity of pepper at these different stages reported increased antioxidant activity with the maturation of peppers, that is, higher antioxidant activity in the red, purple, or yellow peppers compared to immature green peppers (Castro‐Concha et al., 2014; Cervantes‐Paz et al., 2012; Choi et al., 2022; Howard et al., 2000; Jimenez et al., 2003; Kovacs et al., 2022; Manikharda et al., 2018; Sinisgalli et al., 2020). The high antioxidant activity in matured red peppers was identified to be due to the higher content of capsaicinoids, capsinoids, polyphenols, β‐carotene, lycopene, and ascorbic acid (Iqbal et al., 2013; Manikharda et al., 2018; Shukla et al., 2016; Sinisgalli et al., 2020), whereas the highly antioxidant purple pepper had higher polyphenolic and flavonoid contents (Kovacs et al., 2022).…”
Section: Factors Influencing Antioxidant Activity Of Peppermentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a water shortage inhibits the enzymes responsible for hydrolyzing endosperm starch, which supplies energy for plant development by metabolizing sugar [ 17 ]. Water stress, in general, is followed by oxidative stress in seeds during germination, which is characterized by an increase in the production of reactive oxygen species [ 18 , 19 , 20 , 21 ]. Therefore, a combination of the antioxidant activity defense system and the internal content of these substances are essential for successful germination under limited water conditions [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%